2017
DOI: 10.1038/s41598-017-13533-7
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib promotes KHSV and EBV lytic cycle by activating JNK and autophagy

Abstract: KSHV and EBV are gammaherpesviruses strictly linked to human cancers. Even if the majority of cancer cells harbor a latent infection, the few cells that undergo viral replication may contribute to the pathogenesis and maintenance of the virus-associated malignancies. Cytotoxic drugs used for the therapies of cancers harboring virus-infection often have, as side effect, the activation of viral lytic cycle. Therefore it is important to investigate whether they affect viral reactivation and understand the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
(51 reference statements)
0
37
0
Order By: Relevance
“…In addition, we found that the final phases of autophagy were inhibited by EBV, allowing the virus to avoid its own elimination by the lysosomal proteases and to usurp the autophagic machinery for intracellular transportation [ 6 ]. Later on, we have demonstrated that, depending on the lytic cycle inducing treatment, a PKC theta–p38MAPK axis [ 41 ] or JNK1/2 [ 42 ] play a major role in promoting viral replication through the induction of autophagy. Other studies have investigated this aspect of EBV biology, demonstrating that the virus recruits Atg8–LC3 coupled membranes to its envelope in the cytosol, and uses autophagic membranes for efficient envelope acquisition during lytic infection [ 43 ].…”
Section: Ebv Lytic Reactivation and Autophagymentioning
confidence: 99%
“…In addition, we found that the final phases of autophagy were inhibited by EBV, allowing the virus to avoid its own elimination by the lysosomal proteases and to usurp the autophagic machinery for intracellular transportation [ 6 ]. Later on, we have demonstrated that, depending on the lytic cycle inducing treatment, a PKC theta–p38MAPK axis [ 41 ] or JNK1/2 [ 42 ] play a major role in promoting viral replication through the induction of autophagy. Other studies have investigated this aspect of EBV biology, demonstrating that the virus recruits Atg8–LC3 coupled membranes to its envelope in the cytosol, and uses autophagic membranes for efficient envelope acquisition during lytic infection [ 43 ].…”
Section: Ebv Lytic Reactivation and Autophagymentioning
confidence: 99%
“…For HSV-1, IRE1 activation could activate JNK, which has been shown to support viral replication in multiple cell types [101]. JNK has also been shown to play important roles in KSHV infection; de novo infection triggers JNK activation, and ER stress-induced JNK activation can reactivate KSHV from latency [110,111]. Later stages of KSHV lytic replication also feature JNK activation, and ectopic expression experiments have shown that KSHV lytic proteins K15 and vGPCR can induce JNK phosphorylation [112,113].…”
Section: Discussionmentioning
confidence: 99%
“…Recent pathological and molecular findings have led researchers to examine the therapeutic potential of several molecular targeting agents, including proteasome inhibitors, immunomodulatory agents, and PI3K inhibitors [120][121][122][123]. Most results are based on in vitro data, and further evaluation (in prospective clinical trials if possible) is necessary before such agents can be used as a treatment for patients with PTLD.…”
Section: Possible Future Therapymentioning
confidence: 99%